Preparing Graduate Students To Carry Out Their Roles and Responsibilities in a School-Based Setting. - Giess, SallyAnn; Schussler, Kelly Farquharson; Means, Jennifer Walsh; Fitzgerald, Mary Dale (Perspectives on Issues in Higher Education, 2012)
Today's school-based speech-language pathologists (SLPs) serve children across a wide range of communicative disorders and perform duties in a variety of service delivery settings. Student learning outcomes in graduate communication sciences and disorders (CSD) preparation programs must reflect these expanding roles of SLPs as they prepare candidates for practice in the schools. Recognizing this challenge, a committee of SLPs in higher education created the University Outreach Committee (UOC) document. This document puts an ASHA practice policy into action by providing learning outcomes, formative assessments, and artifacts that university academic and clinical faculty can use to prepare graduate CSD students for work in schools.